Case report: A novel mosaic nonsense mutation of PCDH19 in a Chinese male with febrile epilepsy - Chen, Guilan; Zhou, Hang; Lu, Yan; Wang, You; Li, Yingsi; Xue, Jiaxin; Cheng, Ken; Huang, Ruibin; Han, Jin (Frontiers in Neurology, 2022)
The clinical features of the PCDH19 gene mutation include febrile epilepsy ranging from mild to severe, with or without intellectual disability, cognitive impairment, and psych-behavioral disorders, but there has been little research on males with the mosaic mutation of PCDH19. This study reported a novel, de novo, and mosaic PCDH19 nonsense mutation (NM_001184880: c.840C > A, p. Tyr280*) from a Chinese male in early middle childhood by trio whole-exome sequence (Trio-WES) and confirmed by Sanger sequence. The proportion of the mosaic mutation (c.840C > A, p. Tyr280*) in PCDH19 was 27.9% in, buccal mucosal cells, 48.3% in exfoliated cells in the urine, and 50.6% in peripheral blood of proband. He had the first onset of seizures in toddlerhood with febrile epilepsy, mild impaired cognitive psychological, and behavioral abnormalities. The electroencephalography (EEG) exhibited sharp waves and sharp slow complex waves in the bilateral parietal, occipital, and posterior temporal regions during the interictal period. Pinpoint white matter lesions in the periventricular white matter and slightly bulging bilateral ventricles appeared on cranial magnetic resonance imaging (MRI). With Depakine and Keppra he gained good control over his epilepsy. This study might expand the genotypes and broaden the spectrums.